Evaluation of Destination Management at Governor’s Rapid, Quirino Province, Philippines: A Basis for Marketing Development - Belman Millan; Babyjane Casillano; Diana Elizab; Lery Jane A. Baltazar (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study investigates the decline in tourist arrivals at Governor’s Rapid in Quirino Province, Philippines, and evaluates the strategies employed by local stakeholders to promote and manage the site, with the goal of identifying pathways for sustainable ecotourism development. Method: A basic qualitative research design was employed. Data were collected through semi- structured interviews with tourism officers, community members, and visitors, selected via purposive sampling. Thematic analysis was used to identify recurring patterns and themes. Result: The study identified multiple interrelated factors contributing to the decline, including limited infrastructure, weak promotional efforts, environmental degradation, and poor coordination among agencies. Existing initiatives, such as community involvement and occasional tourism campaigns, were found to be fragmented and reactive. The COVID-19 pandemic further disrupted travel behaviors, exacerbating the decline. Contribution: Findings underscore the urgent need for innovative, inclusive, and locally driven tourism management strategies. Recommendations include enhancing destination branding, improving infrastructure and accessibility, fostering stronger stakeholder collaboration, and adopting a resilience-based tourism framework. The study contributes to the broader discourse on rural tourism recovery and offers practical guidance for local policy-making and sustainable tourism development in post-pandemic contexts.